Strategic Orientation of Homestay in Lima Puluh Kota Regency: Market and Technology Perspective - Afifah Afifah; Ranti Komala Dewi; Willson Gustiawan (International Journal of Family Business Practices, 2022)
There are numerous small-scale homestay businesses in the Lima Puluh Kota Regency along with the development of tourist destinations in this region. Several studies have found that small-scale businesses could grow in terms of competition and performance if they have market and technology orientation. This article aims to investigate whether the homestay business in Lima Puluh Kota Regency is market and technology-oriented. This study utilized descriptive analysis research design. The investigation was conducted using questionnaire and interviews on consumer orientation, competitor orientation, technology policy, and position and adoption, which were randomly distributed to 55 homestay business owners as the sample. The questionnaires adopted the scales of Harerro (2018) and Al Ansari et al. (2013), with sound psycometric characteristics. SPSS v26 was used to process the data.  This study found that the owners or managers of the homestay in Lima Puluh Kota Regency have been pretty good market-oriented, and nevertheless in few numbers, among them have a technology orientation. These findings are believed contribute to tourism and family business literature especially in homestay business.